Identifying the Best Fit Failure Distribution and the Parameters of Machine’s Component: A New Approach. - Ahmad, Rosmaini; Kamaruddin, Shahrul; Mokthar, Mohzani; Almanar, Indra Putra (2006)
In industries, failure of the equipment to function became a major contribution to the production losses and high maintenance cost.